Free radicals and redox signalling in T-cells during chronic inflammation and ageing. (21st September 2011) - Griffiths, Helen R.; Dunston, Christopher R.; Bennett, Stuart J.; Grant, Melissa M.; Phillips, Darren C.; Kitas, George D.
Abstract : During chronic inflammation and ageing, the increase in oxidative stress in both intracellular and extracellular compartments is likely to influence local cell functions. Redox changes alter the T-cell proteome in a quantitative and qualitative manner, and post-translational modifications to surface and cytoplasmic proteins by increased reactive species can influence T-cell function. Previously, we have shown that RA (rheumatoid arthritis) T-cells exhibit reduced ROS (reactive oxygen species) production in response to extracellular stimulation compared with age-matched controls, and basal ROS levels [measured as DCF (2′, 7′-dichlorofluorescein) fluorescence] are lower in RA T-cells. In contrast, exposing T-cells in vitro to different extracellular redox environments modulates intracellular signalling and enhances cytokine secretion. Together, these data suggest that a complex relationship exists between intra- and extra-cellular redox compartments which contribute to the T-cell phenotype.